Is self-management a burden? What are the experiences of women self-managing chronic conditions during pregnancy? A systematic review - Jakubowski, BE; Hinton, L; Khaira, J; Roberts, N; McManus, RJ; Tucker, KL (BMJ, 2022)
Objective This systematic review examines the qualitative literature on women’s experiences of self-managing chronic conditions in pregnancy. Design Systematic review of qualitative literature. Searches were performed in PubMed and CINAHL from inception to February 2021. Critical interpretive synthesis informed the coding framework and the analysis of the data. The Burden of Treatment theory emerged during the initial analysis as having the most synergy with the included literature, themes were refined to consider key concepts from this theory. Participants Pregnant women who are self-managing a chronic condition. Results A total of 2695 articles were screened and 25 were reviewed in detail. All 16 included studies concerned diabetes self-management in pregnancy. Common themes coalesced around motivations for, and barriers to, self-management. Women self-managed primarily for the health of their baby. Barriers identified were anxiety, lack of understanding and a lack of support from families and healthcare professionals. Conclusions Pregnant women have different motivating factors for self-management than the general population and further research on a range of self-management of chronic conditions in pregnancy is needed.